Microplastics ingestion by marine fauna with a particular focus on commercial species: a systematic review - Marmara, Dimitra; Katsanevakis, Stelios; Brundo, Maria-Violetta; Tiralongo, Francesco; Ignoto, Sara; Krasakopoulou, Evangelia (Frontiers in Marine Science, 2023)
Over the past few decades, the scientific community has extensively investigated microplastics (MPs) and their interactions with marine organisms. MPs ingestion has been one of the most commonly examined topics across marine fauna. In this study, we present a systematic review conducted to gather information on the MPs ingestion by different taxonomic groups, collect MPs abundances and characteristics, and explore the relative literature evolution. Additionally, through meta-analysis, we focused on marine commercial species, aiming to estimate the mean MPs ingestion quantities in Pisces, Mollusca, Crustacea, and Echinodermata. A total of at least 822 marine species were reported to have ingested MPs for the period of 1972–2021. Pisces (class: Teleostei) was the most frequently examined group including 513 species reported to have ingested at least one MP and exhibited the widest range of mean MPs ingestion quantities [0.07–16.33 MPs per individual (MPs/ind) GIT] among the different families. The studies that analyzed soft tissue focused mainly on Gastropoda, Bivalvia, Malacostraca, and Echinodermata (8.85 MPs/ind, 3.64 MPs/ind, and 1.03 MPs/ind, 1.56 MP/g respectively). In total, MPs’ most frequently found characteristics were fibers, measuring less than 1 mm, black in color, and composed of polyethylene. The wide range of MPs descriptions concerning their characteristics and the notable high heterogeneity of the estimated values of MPs ingestion among and within most families highlights the importance of adopting harmonized methodological protocols to more effectively address the MPs issue.